COMPOSITIONAL FIDELITY AND TAPHONOMY OF FRESHWATER MOLLUSKS FROM THREE PAMPEAN SHALLOW LAKES OF ARGENTINA (Ameghiniana, 2017)
Three shallow lakes from the southeastern pampas, which are different in their physicochemical characteristics, were studied with the aim of comparing live/dead fidelity and preservation of mollusk shells. The studied lakes were Las Mostazas, Los Carpinchos and Nahuel Rucá, which proved different in terms of their specific richness, abundance, compositional fidelity and taphonomic alteration. The lake that presented the higher values of conductivity (3.34±0.72), hardness (286±83 mgl -1) and carbonates saturation index (SI calcite= 1.95±0.21) was the one for which lower specific richness in living assemblages was recorded and differences in richness and diversity between the living and the dead assemblages became apparent. It was also the lake where the number of species was higher in death assemblages (R= 5) than in living communities (R= 2). Such characteristics suggest a higher residence time in the taphonomically active zone. On the other hand, the lakes featuring lower values of the same characteristics (conductivity= 2.2±1.2; 0.8±0.5; hardness= 157±55; 250±127 mgl -1; saturation index of calcite= 0.35±0.15; 0.43±0.36, for LC and NR respectively) presented a higher species richness, lower numbers of species in death assemblages (R= 8) than in living communities (R= 10) and taphonomic attributes that suggested recently dead and deposited individuals. All these results indicate that water conditions in these lakes result in the decrease of the preservation of carbonate remains in comparison with the previously mentioned lake. Even though the lakes are located close to each other and are of similar shape and depth, such differences in water characteristics may be affecting shell preservation. Resumen. FIDELIDAD COMPOSICIONAL Y TAFONOMÍA DE MOLUSCOS DULCEACUÍCOLAS EN TRES LAGOS SOMEROS PAMPEANOS DE ARGENTINA. Se estudiaron tres lagos someros del sudeste bonaerense que exhiben diferencias en las características físico-químicas con el objetivo de comparar la fidelidad vivo/muerto y la preservación de las conchas de moluscos. Los lagos estudiados fueron Las Mostazas, Los Carpinchos y Nahuel Rucá los cuales exhibieron diferencias en la riqueza específica, abundancia, fidelidad composicional y alteración tafonómica. El lago que presentó los mayores valores de conductividad (3.34±0.72), dureza (286±83 mgl -1) e índice de saturación de carbonatos (IScalcita= 1.95±0.21) fue el que registró menor riqueza específica en los ensambles de vivos, diferencias en la riqueza y diversidad entre ensambles de vivos y de muertos. También fue el lago con mayor número de especies en el ensamble de moluscos muertos (R= 5) que en las comunidades vivientes (R= 2), sugiriendo un mayor tiempo de residencia en la zona tafonómicamente activa. Por otro lado, los lagos con menores valores de las mismas características (conductividad= 2.2±1.2; 0.8±0.5; dureza= 157±55; 250±127 mgl -1; índice de saturación de calcita= 0.35±0.15; 0.43±0.36, para LC y NR respectivamente) mostraron una mayor riqueza de especies, menor número de especies en el ensamble de moluscos muertos (R= 8) que en las comunidades vivas (R= 10) y atributos tafonómicos que sugerirían individuos recientemente muertos y depositados. Todos estos resultados sugieren que las condiciones del agua de estos lagos disminuye la preservación de restos calcáreos en comparación con el lago mencionado previamente. Aunque estos lagos están localizados próximos entre ellos y tienen similar forma y profundidad, las diferencias que existen en las características del agua estarían afectando la preservación de las conchas.